The Impact of Aphasia Camp Participation on Quality of Life: A Primary Progressive Aphasia Perspective - Kim, Esther S.; Figeys, Mathieu; Hubbard, H. Isabel; Wilson, Carlee (Seminars in Speech and Language, 2018)
Individuals with primary progressive aphasia (PPA) and their caregivers are at risk for decreased quality of life (QoL) due to their progressive condition. Aphasia camps are an intervention that can improve QoL, yet individuals with PPA are underrepresented at aphasia camps relative to those with poststroke aphasia. The purpose of this exploratory case study was to examine the effect of participation in aphasia camp on the QoL of a couple impacted by PPA. The Living with Aphasia: Framework for Outcome Measurement (A-FROM) was used to guide a semistructured interview with an individual with PPA and her spouse, both of whom had attended the Alberta Aphasia Camp for 4 years. Conventional content analysis with an inductive approach was used to analyze results. Concepts that emerged from the interview were organized into pre-camp, during, and post-camp categories. Aspects of camp that had an effect on post-camp QoL for this couple with PPA included expanding social connections and introduction to new activities. Personal characteristics exhibited by the couple had an impact on their experience of aphasia camp and how they incorporated their experiences into their everyday lives post-camp. Aphasia camps are a participation-based service approach that can benefit people with aphasia regardless of etiology. A consideration of personal factors of potential campers with PPA, and the provision of PPA-specific resources, is recommended for programs such as aphasia camps that incorporate participants with mixed etiologies.
Keywords: PPA; quality of life; aphasia camp; LPAA